Meningkatkan Pemahaman Mahasiswa tentang Konsep Limit Fungsi Satu Variabel Real melalui Pembelajaran Kooperatif - Usman H.B (Universitas Negeri Malang, 2016)
Students' comprehension on the functional limit concept of one real variable is still low, whereas the limit concept is the main basis in learning calculus further. Therefore, a teaching is needed to improve the students' comprehension on the concept mentioned above. This action research was designed to improve students' comprehension on the concept through the implementation of cooperative model of Student Teams-Achievement Divisions (STAD). The result shows that, this model can increase students' comprehension on the functional limit concept of one real variable